2016
DOI: 10.1073/pnas.1606637113
|View full text |Cite
|
Sign up to set email alerts
|

Stacked charge stripes in the quasi-2D trilayer nickelate La 4 Ni 3 O 8

Abstract: The quasi-2D nickelate La 4 Ni 3 O 8 (La-438), consisting of trilayer networks of square planar Ni ions, is a member of the so-called T′ family, which is derived from the Ruddlesden-Popper (R-P) parent compound La 4 Ni 3 O 10−x by removing two oxygen atoms and rearranging the rock salt layers to fluorite-type layers. Although previous studies on polycrystalline samples have identified a 105-K phase transition with a pronounced electronic and magnetic response but weak lattice character, no consensus on the ori… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
102
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(114 citation statements)
references
References 57 publications
(69 reference statements)
8
102
4
Order By: Relevance
“…However, such studies have not been possible until now because of the difficulty of preparing high-quality single crystal samples. This has recently been overcome for trilayer nickelates through the use of special high-pressure floating-zone image furnaces, which now enable single crystals of these nickelates to be prepared 10 . In the planar-trilayer nickelate La 4 Ni 3 O 8 , recent studies 10, 12 have revealed stripe charge ordering with a phase transition at 105 K. As for La 4 Ni 3 O 10 , a charge–density wave instability has been predicted below the metal-to-metal transition around 140 K 13, 14 .…”
Section: Introductionmentioning
confidence: 99%
“…However, such studies have not been possible until now because of the difficulty of preparing high-quality single crystal samples. This has recently been overcome for trilayer nickelates through the use of special high-pressure floating-zone image furnaces, which now enable single crystals of these nickelates to be prepared 10 . In the planar-trilayer nickelate La 4 Ni 3 O 8 , recent studies 10, 12 have revealed stripe charge ordering with a phase transition at 105 K. As for La 4 Ni 3 O 10 , a charge–density wave instability has been predicted below the metal-to-metal transition around 140 K 13, 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The one third depleted geometry that we investigated has recently been shown to be realized as a result of charge stripe ordering in the nickelates 23,24 , so our simulations speak to the conditions for AF order in those materials. The relative strengths of first and second neighbor exchange couplings for nickelates has not yet been addressed.…”
Section: Discussionmentioning
confidence: 83%
“…1, which more directly connects with the notion of 'depletion' and which also fundamentally involves magnetic order, is provided by recent experimental 23 29 .…”
Section: Figmentioning
confidence: 82%
See 1 more Smart Citation
“…The crystal structure of this compound involves square planar NiO 2 trilayers, isoelectronic to the Cu 2+ O 2 layers of the cuprates if the Ni valence were 1+. Further interest in comparing these systems arises from an antiferromagnetic (AFM) phase transition in La 4 Ni 3 O 8 at a Néel temperature T N = 105 K into a state with commensurate spin and charge stripes [4][5][6], similar in some respects to the AFM transition occurring * Present address: Lawrence Livermore National Laboratory, Livermore, California 94550, USA.…”
Section: Introductionmentioning
confidence: 99%